On the meaning of life - Cottingham, John, 1943- (Thinking in action., 2003)
The question 'What is the meaning of life?' is one of the oldest and most difficult questions we have ever asked ourselves. John Cottingham asks why we are so preoccupied with this question and assesses some attempts to answer it.